The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12884-017-1492-4
|View full text |Cite
|
Sign up to set email alerts
|

Composite measures of women’s empowerment and their association with maternal mortality in low-income countries

Abstract: BackgroundMaternal mortality has declined significantly since 1990. While better access to emergency obstetrical care is partially responsible, women’s empowerment might also be a contributing factor. Gender equality composite measures generally include various dimensions of women’s advancement, including educational parity, formal employment, and political participation. In this paper, we compare several composite measures to assess which, if any, are associated with maternal mortality ratios (MMRs) in low-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…The fertility rate rose from 7. 61 in 1980;at 6.62 in 1990;at 5.86 in 2000;at 5.23 in 2010and 4.94 in 2015(Lan and Tavrow, 2017. The decline in fertility in Côte d'Ivoire is not necessarily explained by the successful of the family planning policy because the prevalence rate of modern contraception remains low.…”
Section: The Decline In Fertility In Côte D'ivoirementioning
confidence: 95%
See 1 more Smart Citation
“…The fertility rate rose from 7. 61 in 1980;at 6.62 in 1990;at 5.86 in 2000;at 5.23 in 2010and 4.94 in 2015(Lan and Tavrow, 2017. The decline in fertility in Côte d'Ivoire is not necessarily explained by the successful of the family planning policy because the prevalence rate of modern contraception remains low.…”
Section: The Decline In Fertility In Côte D'ivoirementioning
confidence: 95%
“…Children are also presented as a source of physical security (Vlassoff, 1982). Thus, from 1960 to 1970, the fertility rate went from 7.35 to 7.88 (Lan and Tavrow, 2017). From 1980, the number of children per woman has decreased.…”
Section: The Decline In Fertility In Côte D'ivoirementioning
confidence: 99%
“…Little information is available on the influence of women's empowerment on the mode of childbirth [12]. In most studies, the social context appears to be a crucial determinant of the impact of empowerment on women's health and well-being throughout the childbirth process [13][14][15]. One study that focused on vaginal delivery demonstrated the difficulty of ensuring that women's autonomy is respected and the crucial role of women's empowerment in childbirth regarding access to information, the presentation of self-assertion and a woman's relationship with midwives [16].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, studies either: 1) examine cross-country or regional data [24] or combine household surveys from several countries [5], both of which can make it difficult to clearly identify determinants as there is a great deal of heterogeneity across regions/countries; 2) examine factors affecting uptake of maternal health services rather than maternal death directly [6–13]; or 3) identify cases of maternal death and then append these with a random sample of births (controls) that have not resulted in death [14–20]. Collection of the case data is costly and time-consuming and often only feasible over a limited geographic range and many of these studies are restricted to cases and controls admitted to hospitals or health centres, which are likely to be biased to particular demographics.…”
Section: Introductionmentioning
confidence: 99%